Diversity and density of gingers species (Zingiberaceae) on limestone areas of northern west of Sarawak - Angela, anak George (Universiti Malaysia Sarawak (UNIMAS), 2012)
Limestone areas in Sarawak are rich with plant diversity and play an important role as a habitat of many endemic plant species particularly herbaceous plant. Zingiberaceae is the largest family in order Zingiberales. This family consists of 53 genera with approximately 1200 species. The main objectives of this study are to determine the diversity and density of gingers on three selected limestone areas in northern west of Sarawak, viz. Bau, Padawan and Serian. A total of forty five (45) study plots were set up in studies sites and 10 m X 10 m study plots were established randomly in each sites. Twelve genera and 32 species were recorded during this study. Data were analysed using Shannon’s Weiver Index for species diversity and One-way ANOVA and T-test for density of gingers in study sites. The Shannon’s Weiver Index for Bau, Padawan and Serian is 1.62, 1.59 and 1.50. Genus Etlingera was the most abundant genus found in three studies sites. The most diverse foothill limestones was Gunung Poing and the most diverse studies sites was Bau limestones areas.